EVALUATION OF CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION IN STATE SENIOR HIGH SCHOOLS IN DELI SERDANG REGENCY, NORTH SUMATERA PROVINCE - Panigoran Siburian (CV. RADJA PUBLIKA, 2025)
This study aims to evaluate curriculum management in improving the quality of education in Senior High Schools in Deli Serdang Regency. The focus of the study includes the planning, implementation, and supervision of the curriculum applied in five schools selected by Purposive Sampling. The research approach uses a qualitative method with data collection techniques through in-depth interviews, observations, and documentation studies. Data are analyzed using an interactive model involving data reduction, data presentation, and drawing conclusions. The results of the study indicate that curriculum planning in Senior High Schools in Deli Serdang Regency has referred to national education standards, but there are still challenges in adjusting the curriculum to local needs. The implementation of the curriculum is going quite well, but faces obstacles in the availability of resources, such as competent teaching staff and supporting facilities. Curriculum supervision is carried out periodically, but still needs strengthening to ensure consistency between planning and implementation. Therefore, curriculum management has an important role in improving the quality of education, but further efforts are needed to improve synergy between stakeholders, empower teachers, and optimize supporting facilities. This study recommends a strategy for improving curriculum management based on collaboration to support higher quality education that is relevant to the needs of the community in Deli Serdang Regency.